Soil fertility affects the growth, nutrition and yield of cotton cultivated in two irrigation systems and different nitrogen rates. - Santillano Cázares, Jesús; Roque Díaz, Luis Guadalupe; Núñez Ramírez, Fidel; Grijalva Contreras, Raúl Leonel; Robles Contreras, Fabián; Macías Duarte, Rubén; Escobosa García, Isabel; Cárdenas Salazar, Víctor (REVISTA TERRA LATINOAMERICANA, 2019)
Intrinsic soil fertility and the method of irrigation can affect the efficiency of nitrogen (N) fertilization, modify the yield goal, growth, and nutritional status of crops. A study was carried out with the objective of determining yield, growth, water use efficiency (WUE), agronomic efficiency of N (AEN), NO3- concentration in petiole cell extract (PCE) and chlorophyll index (SPAD) in a cotton crop by effect of N rates and two irrigation methods. The study consisted of two experiments established in soils of high fertility [˃13 g kg-1 organic matter (OM) and N-NO3- ˃ 30 mg kg], with varying N fertilization rates: a) flood irrigation (FRR, 11 and 220 kg N ha‑1), and b) drip irrigation (FRG, 11 to 440 kg N ha-1). Plant height and number of nodes were not affected by the applied treatments. SPAD values and NO3- concentrations in PCE were cubically related to crop yield. The highest yield and WUE was obtained in the experiment with drip irrigation. In the FRR experiment no response (P > 0.05) to N fertilization treatments was found. In the FRG experiment, application of 440 kg N ha‑1 reduced yield by 43% compared to the rest of the evaluated rates. AEN was statistically higher (P < 0.001) in treatments fertilized with 11 kg N ha‑1. The low yield response due to application of N in cotton was attributed to high concentrations of N-NO3- and OM that are present in the soils in which the experiments were conducted.